Is there an Effect of Mono Thermotherapy Regarding Functional Health and Quality of Life? A Randomized Controlled Cross-over Trial to Compare Ultrasound and Laser Therapy - Best, N.; Loppar, A.; Best, S.; Derlien, S.; Glöckner, M.; Bocker, B. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2015)
Aim of the study: Proof of efficacy of ultrasound respectively laser therapy on pain of the lumbar spine or the shoulder with regards to quality of life.Methods: 20 patients with lumbar or shoulder pain were randomized and included in a cross-over design. After 2 weeks of treatment with either ultrasound or laser the patients crossed over to the other according therapy. At 5 time points SF-36 and EQ-5D were used as generic assessments for determination of quality of life and functional health.Results: The SF-36 shows a tendential improvement in the physical summary score and in the item bodily pain, but no changes in the mental summary score. The EQ-5D shows a positive development by trend over the entire period of examination. The clinical function parameters improved over the study period.Conclusions: Laser and ultrasound as monotherapy may lead to an improvement of functional health and quality of life.
Keywords: high intensity laser; ultrasound; mono thermotherapy; quality of life; effectiveness